Macroeconomic and firm-specific determinants of financial performance: Evidence from non-life insurance companies in Africa - Thabiso Sthembiso Msomi (Cogent Business & Management)
This study aimed to examine the macroeconomic and firm-specific determinants of financial performance using 121 listed non-life insurance companies from 48 African countries for the period 2008–2019. Panel data of 1452 observations were examined using both ordinary least squares and two-step System Generalised Method of Moments estimators. The findings of this study show that lagged return on assets, equity capital, operational efficiency and leverage, investment capability and gross domestic product are the statistically significant determinants of financial performance in African non-life insurance companies even though equity capital, operational efficiency and leverage are inversely significant. It is concluded that insurance industries, policymakers, government and investors should take into consideration these significant factors in taking decision and improving their performance. Also, it is recommended that the capital structures of the sector should be restructured to maintain a favourable balance in the equity and debt of the companies. Also, mechanisms such as automated systems that can reduce operational cost should be adopted such that financial performance can be enhanced.